Lactobacillus plantarum lab12- and lactobacillus casei lab13- induced neuropprotection was associated, at least in part, with increased neurotransmission, anti-oxidant and decreased neuroinflammation in app transgenic mice / Nor Amalina Ahmad Alwi - Ahmad Alwi, Nor Amalina (2018)
Bidirectional signalling between the gut and the brain plays essential role in maintaining homeostasis of our body. This interesting concept of gut-brain axis has led to discovery of gut microbiota-modulated neuroprotection. The mechanisms underlying this newly uncovered therapeutic effect remain poorly understood. Alzheimer's disease (AD) is a neurodegenerative disorder that poses vicious threats to health and well-being of the ageing world population. It is characterised by increased oxidative stress and neuroinflammation, as well as reduced neurotransmission. Currently, there is increasing evidence regarding the effective use of probiotics or beneficial bacteria as neuroprotective agents against AD. The present study had successfully elucidated mechanisms underpinning neuroprotection induced by the unique Lactobacillus plantarum (LAB 12) and the commercialized Lactobacillus casei strain Shirota (LAB 13) using APP transgenic mouse model. The mice (male; 10-12 months old) were treated with LAB 12 (n = 6) and LAB 13 (n = 6), respectively (109 CFU/mL, p.o) over a period of 12 weeks before being subjected to behavioural study using the Morris Water Maze Test. The transgenic rodents were then sacrificed and brains were removed. Brain homogenates were subjected to amyloidogenic genes expression, cholinergic, antioxidative and anti-inflammatory tests. Results from the behavioural study indicated enhanced memory and learning abilities in LAB supplemented groups. LAB-supplemented transgenic mice yielded reduced escape latency and distance over three consecutive days when compared to their APP control and wild type counterparts. The time spent by LAB 12- and LAB 13-supplemented mice in platform zone during Probe Test was significantly (p < 0.05) increased by 57% and 66%, respectively. In term of the amyloidogenic pathway, LAB 12 and LAB 13 inhibited BACE1 (+28% vs +20%) and APP (-42% vs -44%), both of which are contributors to A0 production. Unlike LAB 12 which had exhibited no significant effect on the cholinergic pathway, LAB 13 significantly increased the neurotransmitter, ACh (+23%;/? < 0.01), and significantly reduced AChE (-13%;/? < 0.05) that degrades ACh. Whilst LAB 13 increased CAT (+33%; p < 0.01) and GPx (+43%; p < 0.05), LAB 12 increased CAT (+27%; p < 0.05) and GSH (+40%; p < 0.05), all of which are excellent antioxidant enzymes that protect against oxidative stress (i.e. NO). The up-regulated antioxidant enzymes might have suppressed oxidative stress in the brain given the nitric oxide (NO) level in LAB 12- and LAB 13- supplemented groups that was significantly (p < 0.05) reduced by 50% and 75%, respectively when compared to control. Whilst there were modest changes amongst the tested pro-inflammatory cytokines (IFN-y, IL-ip and IL-6), the anti-inflammatory IL-10 was significantly (p < 0.01) up-regulated in LAB-supplemented groups as opposed to control. IL-10 was found to be increased by 21% and 25% in transgenic mice fed with LAB 12 and LAB 13, respectively. Altogether, the LAB-induced neuroprotection could be mediated, at least in part, through regulation of cholinergic activity, anti-oxidative activity and anti-inflammatory activity. The present findings provide important insights into design of therapy that can further enhance LAB induced neuroprotection in AD.